Fire, environmental and anthropogenic controls on pantropical tree cover - Douglas I. Kelley; France Gerard; Ning Dong; Chantelle Burton; Arthur Argles; Guangqi Li; Rhys Whitley; Toby R. Marthews; Eddy Roberston; Graham P. Weedon; Gitta Lasslop; Richard J. Ellis; et al. (Communications Earth & Environment)
Abstract Explaining tropical tree cover distribution in areas of intermediate rainfall is challenging, with fire’s role in limiting tree cover particularly controversial. We use a novel Bayesian approach to provide observational constraints on the strength of the influence of humans, fire, rainfall seasonality, heat stress, and wind throw on tropical tree cover. Rainfall has the largest relative impact on tree cover (11.6–39.6%), followed by direct human pressures (29.8–36.8%), heat stress (10.5–23.3%) and rainfall seasonality (6.3–22.8%). Fire has a smaller impact (0.2–3.2%) than other stresses, increasing to 0.3–5.2% when excluding human influence. However, we found a potential vulnerability of eastern Amazon and Indonesian forests to fire, with up to 2% forest loss for a 1% increase in burnt area. Our results suggest that vegetation models should focus on fire development for emerging fire regimes in tropical forests and revisit the linkages between rainfall, non-fire disturbances, land use and broad-scale vegetation distributions.